PERCEPTION STUDY ON THE EFFECTS OF INTEREST-FREE FINANCING OF ISLAMIC BANKING ON INFORMATION ASYMMETRY AMONG ENTREPRENEURS: EVIDENCE FROM NIGERIA (International Journal of Islamic Business, 2022)
This study investigates the perception of the relationship between interest-free financing contracts of Islamic banking as an incentive to provide voluntary information disclosure among entrepreneurs in Nigeria thereby reducing the incidence of information asymmetry. Questionnaires were used as an instrument of data collection. Multivariate Logistic Regression Model was employed to estimate the model. The result showed a positive and significant relationship between the incentive of interest-free financing contracts and motivation to give voluntary information disclosure, thereby minimizing the incidence of asymmetric information. Similarly, the finding also indicates that level of education, understanding and awareness of the procedures of obtaining credit facilities from banks (both conventional and non-interest banks) has a significant relationship with the entrepreneurs’ motivation to give voluntary information disclosure to the banks concerning the financing contracts obtained from Islamic banks. However, the religious belief of the entrepreneurs did not indicate a significant relationship with their decisions to have a banking relationship with Islamic banks but was largely motivated by economic factors and business decisions in their relationship with the banks and their motivation to give voluntary information disclosure. This study, unlike most previous studies on Islamic banking in Nigeria, investigates the perception of entrepreneurs of the relationship between the incentive of interest-free financing contracts and motivation to volunteer greater information. The policymakers can, therefore, leverage the positive perception of entrepreneurs of the incentive of interest-free financing, to reduce information asymmetry in Islamic banking, and promote the establishment of more Islamic banks through appropriate legislations and regulations that can ensure enabling operating environment. This would, in turn, promote financial inclusion and reduce the widening funding gap experienced by small and medium enterprises in the country.